HISTORY OF CREATION OF PEDAGOGICAL SCIENCE AND CHARACTERISTICS OF RELATIONSHIP WITH OTHER DISCIPLINES - Marayimova Kibriyokhan, Muhammadjonova Ogiloy (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, information about the science of pedagogy and scientists who made a great contribution to the science of pedagogy and the relationship of this science with other disciplines and the history of injury are given, and information is also given about the goals and tasks of the science of pedagogy. passed.